Embodied education: Senses, emotions, and technology - Silva, Maria Joao; Ferreira, Eduarda; Andrade, Vania; Nunes, Olinda; Da Luz Carvalho, Maria (2015 International Symposium on Computers in Education (SIIE), 2015)
The theme of this paper is the importance of educational embodied approaches, aiming at developing children's sensory awareness, emotional competences and abstract thinking. The case studies presented in this paper explored the joint use of human senses and electronic sensors in embodied educational activities, related to mathematics and science education, situated in schools and in the schools' neighbourhood, and grounded in children's everyday practices. In all the three case studies, the children enhanced sensory and emotional awareness, body literacy and developed abstract thinking, grounded on their own embodied experiences.